2007
DOI: 10.1016/j.vaccine.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral vaccination of raccoons (Procyon lotor) with genetically modified rabies virus vaccines

Abstract: Oral vaccination is an important tool currently in use to control the spread of rabies in wildlife populations in various programs around the world. Oral rabies vaccination (ORV) of raccoons represents the largest targeted program to control wildlife rabies in the United States. Currently, the vaccinia-rabies glycoprotein recombinant virus vaccine (V-RG) is the only licensed oral rabies vaccine in the US. In the current study, captive raccoons were used to evaluate two previously described constructs of a rabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Although we cannot rule out the contribution of other factors, such as cell-mediated immune responses (Nathanson and Gonzalez-Scarano, 1991;Lambot et al, 2001), to survival of some animals in the absence of a strong humoral immune response, the fact that a similar proportion of control animals also survived suggests that survival of these vaccinates was not due to immunization. The challenge virus dose was chosen to result in a minimum of 80% mortality in the nonvaccinated group as per Title 9, Part 113 of the Code of Federal Regulations (CFR, 2010); therefore, the presence of survivors in the control group was not unexpected and also has been reported in other studies (Black and Lawson, 1970;Rupprecht et al, 1988Rupprecht et al, , 1993Sé tien et al, 1998;Blanton et al, 2007;Henderson et al, 2009;Mü ller et al, 2009). Despite clear differences between the vaccines in composition and route of administration, the effect of the humoral immune response, once initiated, was similar with respect to protection from disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although we cannot rule out the contribution of other factors, such as cell-mediated immune responses (Nathanson and Gonzalez-Scarano, 1991;Lambot et al, 2001), to survival of some animals in the absence of a strong humoral immune response, the fact that a similar proportion of control animals also survived suggests that survival of these vaccinates was not due to immunization. The challenge virus dose was chosen to result in a minimum of 80% mortality in the nonvaccinated group as per Title 9, Part 113 of the Code of Federal Regulations (CFR, 2010); therefore, the presence of survivors in the control group was not unexpected and also has been reported in other studies (Black and Lawson, 1970;Rupprecht et al, 1988Rupprecht et al, , 1993Sé tien et al, 1998;Blanton et al, 2007;Henderson et al, 2009;Mü ller et al, 2009). Despite clear differences between the vaccines in composition and route of administration, the effect of the humoral immune response, once initiated, was similar with respect to protection from disease.…”
Section: Discussionmentioning
confidence: 90%
“…Different study environments (laboratory and field), experimental designs, and vaccine presentation methods (bait vs. oral) are also complicating factors. Laboratory studies of VRG immunogenicity reporting seroconversion rates approaching 100% involved either direct instillation of the vaccine into the oral cavity (Blanton et al, 2007) or ingestion of vaccine via polyurethane sponge baits (Rupprecht et al, 1986(Rupprecht et al, , 1988. Seroconversion rates of 60-70% were reported in field studies when VRG was dispensed in a wax ampule inserted into a fishmeal polymer (FP) bait (Hanlon et al, 1998;Roscoe et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in mongooses using very similar constructs showed that the presence of VNA was indicative for protective immunity (Blanton et al, 2006). SPBN GASGAS has been tested in other species such as raccoons, and animals with VNA were consistently protected against a relevant rabies infection (Blanton et al, 2007). Therefore, no challenge infection was performed.…”
Section: 0000298-v1)mentioning
confidence: 99%
“…Positive VNA titers (!0.06 IU=mL) were demonstrated by complete neutralization of the challenge virus dose (50 focus forming doses) at a 1:4 serum dilution. The choice of this cutoff value follows previous studies for Lyssavirus surveillance using bat and nonbat sera (Shankar et al 2004, Lumlertdacha et al 2005, Blanton et al 2007, Jackson et al 2008. A previous study has demonstrated that the immunoglobulin G fraction of the bat serum is responsible for neutralization activity against RABV (Shankar et al 2004).…”
Section: Detection Of Rabv Neutralizing Antibodiesmentioning
confidence: 99%